Multidimensional poverty measurement at Malaysian Zakat Institutions: monetary and non-monetary indicators / Arifin Md Salleh ... [et al.] - Md Salleh, Arifin; Abdul Rasool, Mohamed Saladin; Mohd Harun, Mohd Fauzi; Ahmad, Sanep (2012)
In practice, zakat institutions in Malaysia use the monetary approach in measuring poverty through the conventional Poverty Line Income (PLI) and Had al Kifayah (necessities of a household) methods. PLI is set by the Economic Planning Unit (EPU) of the Prime Minister Department wheras each zakat institutions determined their had al kifayah respectively. Economists have argued that the current poverty measures using monetary pproach is not able to reflect the multidimensional nature of povert which has developed due to the rapid economic development process and changes of the economic structure (Nair. 2000). Unfortunately, there is no such effort has been taken by zakat institutions to use this approach Thus. there is a need to look at poverty from the multidimensional outlook, taking into account non-monetary approach and Islamic indicators to determine the poor. Hence. poverty could be analyzed in a more comprehensive dimension by the policy makers. The objective of the research is to formulate an Islamic Poverty Indicator (lPI) as an alternative poverty measurement. The IPI which incorporates monetary and nonmonetary indicators comprising of of maqasid-al sharia (objective of the religion) elements, namely religion. knowiedge, physical-self. offspring and wealth that is envisaged to reflect the multidimensional ohenomenon of poverty in a more holistic way. The exploratory research would employ primary data through expert opinion and survey using questionnaire to respondents among poverty group. The method of expert opinion as thre is no previous validated used to formulate an IPI. The conceptual framework of the research would be adopted from the works of Mohd Fauzi Harull (2007), Islamic Relief (2008) and Rosbi and Sanep (2010). The proposed IPI is expected to give an alternative of measuring poveriy to zakat institutions to identify a more holistic poverty group